Model HOT-Fit Pada Analisa Faktor- Faktor Penggunaan E-Commerce Berbasis Android - Dewi Lusiana; Agung Nilogiri (Faculty of Computer Science, University of Jember, 2023)
E-Commerce is beneficial for micro, small and medium enterprises in selling their products. Initially, sales were only made offline; now, they can be done online. The HOT (Human, Organization, Technology) Fit Evaluation Framework is used to evaluate Android-based micro, small and medium business E-Commerce applications. This study analyzes the effect of service quality on user satisfaction and the effect of user satisfaction and organization on net benefits. It is to provide information about the level of perceptions of Android-based E-Commerce users in its implementation. The results of data analysis were conducted using the Structural Equation Model (SEM). The quality of Service (KL) of Android-based e-commerce significantly affects User Satisfaction (KP). The coefficient value is 0.760, and the CR is 6,780 more than the required critical value of 1.96. It indicates that Service Quality has a significant effect on User Satisfaction. User Satisfaction has a significant effect on Net Benefits. The coefficient value is 0.492, and the CR is 5.511, more than the required critical value of 1.96. It states that User Satisfaction has a significant effect on Net Benefit. Organizational structure has a significant effect on Net Benefit. The coefficient value is 0.547, and the CR of 5.246 is more than the required critical value of 1.96. It means that the Organizational Structure has a significant effect on Net Benefit. TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back //